PERUBAHAN pH, C-ORGANIK DAN N TOTAL TANAH MASAM PADA PERTANAMAN BUNCIS SETELAH PEMBERIAN PUPUK KANDANG DI KAMBU, KENDARI - Suleman, Darwis; Alam, Syamsu (Institute of Computer Science (IOCS), 2024)
Acid soils such as Ultisol has many constrains for the development of greenbean such as low pH, organic C, CEC and low nutrients available. In this context, the use of manure is an alternative to improve soil quality and increase the productivity of greenbean. A study was carried out at the Experimental Farm of the Faculty of Agriculture, Halu Oleo University on which the study aimed to evaluate the effect of manure and dosage on soil pH, organic C and total-N as well as the yield of greenbean. The study was laid out in a Split-plot design with three replications. The main plot consisted of three types of manure (chicken, goat and cow). The subplots, namely fertilizer doses, consisted of: without manure serve as a control, 200 g of polybeg-1, 400 g of polibeg-1 and 600 g of polibeg-1. The results highlighted that the type of manure has different effect on soil pH, organic C and total-N. The highest soil pH and organic C were recorded when applying 600 g polibeg-1 of chicken manure, while the highest of total-N was observed when applying 600 g of polibeg-1 of cow manure. The type of manure and application rate increased significantly the yield of greenbean, but no interaction was observed. This study concluded that the application of goat and chicken manure at the rate of 200 – 400 g polybeg-1 enhanced significantly the yield of greenbean.